WOW Customer Loyalty dan Emotional Talk Service: sebuah Survey di Mall Galeria - Daniel Saputra Tanumihardja (Universitas Pendidikan Nasional, 2017)
ABSTRACTIn Indonesia the franchise rights BreadTalk bought by Johnny Andrean because he believed that BreadTalk can grow and developin Indonesia. Isa premium boutique bakery Bread Talk first to bring the concept of an open kitchen with a modern style. This concept allows BreadTalk to make bread directly on the spot so that the manufacturing process can be seen directly by the customer and received bread will always be fresh.Consideration used in selecting respondents is as follows respondent is the customer with a minimum education level of high school or equivalent. Respondents are customers who frequently shop at BreadTalk Mall Bali Galeria with consideration to properly assess the products and services BreadTalk.The results of statistical data analysis showed that the Productivity positive and significant impact on the Customer Loyalty WOW customers with e- Talkin BreadTalk Mall Bali Galeria. Brand Image positive and significant impact on Brand Trust customers BreadTalk Mal Bali Galeria. Brand Trust positive and significant impact on the Customer Loyalty WOW customers with e-Talkin BreadTalk Mall Bali Galeria. Creativity positive and significant impact on the Customer Loyalty WOW customers with e-Talk in BreadTalk Mall Bali Galeria.Consumer dissatisfaction with productivity can be seen in the quantity dimension. Brand image can be seen on the dimensions strengthness. Brand trust can be seen in the dimension of brand reliabilty. Creativity can be seen on the dimensions off lexibility of thinking. This dissatisfaction must be improved and enhanced for the sake of customer loyalty to the BreadTalk in Mal Bali Galeria.